PENGARUH SELF-EFFICACY DAN ADVERSITY QUOTIENT TERHADAP INTENSI BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN BISNIS UNIVERSITAS NEGERI SURABAYA - Septyan Budy Cahya; Farhan Rachmat Widianto (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Indonesia is one of the most populous countries in the world, yet it still faces serious challenges such as a high unemployment rate. One strategic solution to this issue is entrepreneurship. As future leaders, university students are expected to have a strong entrepreneurial intention. This study aims to analyze the influence of self-efficacy and adversity quotient on the entrepreneurial intention of students in the Business Education Program at Universitas Negeri Surabaya. This research uses a quantitative approach with a survey method through an online questionnaire. A total of 205 students participated, and the data were analyzed using IBM SPSS Statistics 25. The t-test results indicate that both self-efficacy and adversity quotient significantly influence entrepreneurial intention, with a value of 0.000 (<0.05). The F-test also confirms a simultaneous effect of both variables (F = 56.244; sig = 0.000). The coefficient of determination (R²) is 0.351, meaning that 35.1% of the variation in entrepreneurial intention is explained by self-efficacy and adversity quotient. These findings highlight that confidence in one's abilities and resilience in facing adversity are essential psychological factors that drive students' intentions to become entrepreneurs.